Research on the feasibility of distributed vibration sensing technology for leakage detection in diaphragm wall joint - Zhou, Lingyan; Chen, Mingyin; Zhang, Yayong (Frontiers in Physics, 2026)
The integrity of diaphragm walls is of paramount importance to the safety of foundation pits; leakage can readily induce issues such as instability and heave, necessitating efficient and precise detection. This study conductsl aboratory model tests based on Distributed Acoustic Sensing (DAS) technology to investigate the applicability of active and passive methods in leakage identification, as well as the effects of leakage magnitude, sensing optical cable layout positions, and boundary conditions. The results indicate that DAS can effectively identify leakage through acoustic vibration characteristics: the passive method exhibits distinct leakage characteristic signals at 10.25 Hz and 20.25 Hz, with leakage velocity showing a linear positive correlation with peak amplitude; the active method identifies leakage via an external vibration source, and when the spacing between the sensing optical cable and the leakage channel exceeds 50 cm or the channel depth is less than 5 cm, signal attenuation occurs and distinguishability decreases. This study validates the feasibility of DAS technology, providing a scientific basis for real-time distributed leakage detection in foundation pit engineering.